2019
DOI: 10.1590/rbz4820170329
|View full text |Cite
|
Sign up to set email alerts
|

Organic minerals with different chemical characteristics in diets for Hy-Line White laying hens: performance, biometry of digestive organs, and bone quality

Abstract: Two trials were carried out to evaluate the effect of groups of organic minerals with different chemical characteristics on the performance, egg quality, biometry of digestive organs, and bone quality of laying hens in the first and second laying cycles. In the first cycle, 180 layers at 72 weeks were used in a completely randomized design (CRD) with four treatments and five replicates with nine birds each. In the second cycle, 216 layers at 94 weeks of age were used in a CRD with four treatments and six repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have refuted the hypothesis that trace mineral supplementation influences laying hen performance [13,[19][20][21]. However, our study found that AACM supplementation had a favorable impact on laying and feed efficiency.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have refuted the hypothesis that trace mineral supplementation influences laying hen performance [13,[19][20][21]. However, our study found that AACM supplementation had a favorable impact on laying and feed efficiency.…”
Section: Discussioncontrasting
confidence: 73%
“…The biometric analysis of the digestive organs makes it possible to identify probable changes arising from the nutritional management to which the birds were subjected, as the development of these organs is directly related to the animal's food (Farias et al, 2019). Considering the use of superdosing (900 FTUs) of enzymes in the diets, changes in the digestive organs, could evidence adverse effects of such ingredients, therefore making their use unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…A biometric analysis of digestive organs enables identifying possible changes arising from the nutritional management to which the birds were subjected, as the development of these organs is directly related to the animal's feed (Farias et al, 2019). Considering the use of N GP in the feed of pullets, changes in digestive organs could show harmful effects of such ingredients, therefore making their use in birds' diets unfeasible (Li et al, 2018).…”
Section: Natural Growth Promoters Replacing Traditional Growth Promot...mentioning
confidence: 99%